التغيرات الفصلية للهطل المطري في سورية - عمَّار غطفان (Latakia University Journal -Engineering Sciences Series, 2019)
أصبحت مشكلة المياه تتصدر اهتمام سكان العالم, وخصوصاً الأقطار العربية, ومن ضمنها سورية إذ إنَّ النقص في الموارد المائية اللازمة لتوفير الاحتياجات المتزايدة للزراعة والصناعة ومياه الشرب للمواطنين لمعظم هذه الأقطار أصبحت حقيقة يمكن ملاحظتها في الوقت الحاضر. تهدف الدراسة إلى تحديد الانحراف لكميات الأمطار الفصلية عن معدلها العام في سورية، للاستفادة منها أثناء التخطيط لتنفيذ مشاريع التنمية الوطنية. اعتمدت الدراسة على بيانات الهطل المطري الشهرية في ست محطات رصد جوي تنتشر في مناطق مختلفة مناخياً في سورية. واستُخدمت طريقة المتوسط المتحرك في تحديد انحراف كميات الهطل الفصلية عن معدلها العام . توصلت الدراسة إلى وجود تناقص في الهطل المطري خلال فصلي الشتاء والربيع, وإلى وجود تزايد في فصلي الصيف والخريف في المناطق الجافة وشبه الجافة، أمَّا في المناطق الرطبة ونصف الرطبة، فالتزايد يحصل في فصل الصيف فقط، والتناقص في الفصول الثلاثة الأخرى، وكذلك وجود دورية في هذه المحطات، تراوح زمن العودة فيها بين 17 و 30 عاماً، أي إن الدورة الهيدرولوجية تستمر25 عاماً تقريباً. The water problem is a high priority for people, particularly in the Arab countries including Syria. Shortage in water resources needed for the growing demand of agriculture industry and drinking water for citizens in most of these countries is a fact and it can be noticed at the present time. The study defines the deviation of seasonal rain fall amounts from their general mean in Syria in order to use the results in planning for the implementation of the projects of national development. The study depended upon the data of monthly rain fall in six meteorological stations, scattered over different heights above sea level. The method of movable mean has been used to specify the deviation of seasonal rainfall amounts from their general average. The study has shown the existence of general rainfall decrease during winter, spring, and increase in summer, autumn, in the dry zones and semi-dry zones. In the wet zones and semi wet zones, rainfall increase in summer only, and decrease during other seasons, and the existence of a periodicity in these stations which has a return period of 23 year.